Pelatihan Produksi Krupuk dari Ampas Tahu untuk Meningkatkan Produktivitas Pada Anggota PKK - Riyanto Riyanto; Aryan Eka Prastya Nugraha; Novika Wahyuhastuti; Inayah Adi Sari (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The purpose of this service is to facilitate PKK members in Krobokan Village there are several large tofu making factories. UMKM tofu producers in Krobokan Village from the last few years have experienced a fairly high increase in production. This is because the level of public consumption of tofu has increased. The increase in tofu production is offset by an increase in the residual value of production, namely tofu pulp. Tofu waste, which is known to still have a lot of nutritional content, has not been optimally utilized, apart from being made into animal feed. This condition became the idea of the PKK members of Krobokan Village to create alternative products from tofu dregs. This activity was carried out by providing entrepreneurial training to PKK members to produce tofu pulp into crackers and nuggets. The result of this community service activity is that the PKK members of Krobokan Village gain knowledge and skills about utilizing tofu dregs into food that is delicious, nutritious and has economic selling value.